Ultrasonic cavitation processing of diesel fuel - Xintai, Su; Baikenov, M.I.; Tateeva, A.B.; Matayeva, A.Zh.; Essebayev, B.; Madreimov, A.; Mukysheva, G.; Berzhanova, R.S.; Sarsembaev, B.Sh. (KSU Publ., 2014)
The influence of ultrasonic cavitation on diesel fraction of oil in the presence of iron-based catalysts was investigated to identify the chemical transformations of hydrocarbons and clarify possible practical applications of cavitation for oil cracking processes. The change of individual chemical composition of diesel fuel is established at the aspect of increase the amount of light fractions.
Дизельді отынның ультрадыбыстық кавитациялық өңдеуі
Ульразвуковая кавитационная обработка дизельного топлива
Keywords: ultrasound cavitation processing; diesel fuel; cracking process; chemical transformations of hydrocarbons; individual chemical composition of diesel fuel